"And all who joined them": A faithful Christian reading of Esther in a post-Shoah world. (May 2021) - Gaines Walton, Julie
Esther is, first and foremost, a narrative written by and for the Jewish people, a story the Jewish people have told to and about themselves for centuries. Esther is also a story Christians have frequently interpreted out of context. Christians can avoid culturally appropriating this narrative for their own purposes by committing to situate the story of Esther and the Jewish people in its original context, firmly in the center of any interpretation of the text. Modern readers find their place in the narrative in Esth 9:26-28, among "all who joined" the Jews in observing, remembering, and commemorating the events of the book of Esther, celebrated in the Jewish festival of Purim.